The implementation of the contextual learning approach in Akidah Akhlak lesson in Madrasah Tsanawiyah Alfalah Tarutung - Tarigan, Asnita Sari; Simanjuntak, Saidah Fatimah Sari (Universitas Ahmad Dahlan, 2023)
Akidah Akhlak lesson is a subject aimed at internalizing the cognitive component, specifically related to cultivating and developing the concepts of divinity and humanity within students. To effectively foster Islamic character formation, a learning method that aligns with learning objectives and the student's developmental level is required. This study focuses on analyzing the implementation of contextual learning approaches in Akidah Akhlak lessons at Madrasah Tsanawiyah Alfalah Tarutung. The research employs a descriptive qualitative research method. Data collection involves observation, interviews, and documentation. Informants were selected through purposive sampling in January 2022. Data analysis relies on descriptive analysis techniques. The findings reveal that Akidah Akhlak learning is structured using contextual learning methods, incorporating components such as constructivism, inquiry, questioning, community learning, modeling, reflection, and authentic assessment. Applying a contextual approach to Akidah Akhlak learning contributes to shaping Islamic character among students. However, several challenges exist in practice, including difficulties in analyzing individual differences using a contextual approach, evaluating learning outcomes, and managing learning time effectively due to its time-intensive nature.